X‐ray fluorescence of archived bone samples: are raised Pb levels a chance finding or an association with Paget's disease?2. (23rd March 2015) - Egden, Lesley M; Nguyen, Khanh; Chettle, David R; Butler, Richard; Inskip, Michael J; Webber, Colin E
<x xml:space="preserve">Abstract</x> The K‐shell X‐ray fluorescence technique that was developed for measurement of lead in bone in living human subjects was applied to measurement of lead in archived human bone samples. The skull from a person who had suffered from Paget's disease was found to have lead concentrations of 97.5±3.6–532.2±3.2 µg Pb/g bone mineral. A femur sample from a different person, who had also suffered from Paget's disease, had a lead concentration of 18–43.5 with uncertainties between 1.6 and 2.0 µg Pb/g bone mineral. The skull lead concentrations were highly raised compared with findings from in vivo bone Pb measurements, whereas the femur lead concentrations were somewhat raised. In the past, the hypothesis has been put forward that lead can be involved in the etiology of Paget's disease; however, other reports in the literature have not supported that hypothesis. The current findings, while intriguing, are too few to be in any way conclusive but merit further study. Copyright © 2015 John Wiley & Sons, Ltd.